A review on the promising fuel of the future – Biobutanol; the hindrances and future perspectives. (1st November 2022) - Liu, Yuchen; Yuan, Yan; Ramya, Ganesan; Mohan Singh, Shiv; Thuy Lan Chi, Nguyen; Pugazhendhi, Arivalagan; Xia, Changlei; Mathimani, Thangavel
Graphical abstract: Highlights: Global market and scope for Biobutanol as an alternative fuel is analysed. Biobutanol formation from I, II and III generation Biomass is elaborated. Different strategies used in Biobutanol synthesis of covered. Hindrances in Biobutanol generation are focussed. Properties of Biobutnaol vs biofuels and fossil fuels are compared. Modifications demonstrated in application of Biobutanol are provided. Abstract: Biobutanol is considered to be the new generation fuel and it is reported to be an efficient fuel than the other known biofuels due to its both physical and chemical features. The anaerobic fermentation of lignocellulosic biomass is the possible route for the production of biobutanol. The hindrances faced in the production of biobutanol are the cost of production, time consumption, and sporulation stage, which blocks the solvent production. Several works have focused to reduce the difficulties and challenges in biobutanol production. The preparation methodology, reactor designs, and genetically engineered microbes have definitely shown the solution to the problems. In this connection, this review will detail the existing troubles faced during biobutanol production, and the overview of research activities proposed to solve the troubles were also presented. The comprehensive look of production methodologies is briefly explained and the recent genetic engineering approaches and computational ways to improve biobutanol production are covered. Further, the characteristics, engine compatibility of biobutanol, and difficulties towards its commercialization were also projected.